Archived Model Output for "Simulating Observations of Southern Ocean Clouds and Implications for Climate" - McCluskey, Christina (Zenodo, 2022)
This is an archive of CAM6 simulation output used in the paperSouthern Ocean Aerosol and Ice Nucleating Particles in the Community Earth System Model Version 2, submitted to the Journal of Geophysical Research Atmospheres.